A Proposal to Remove Some Disequilibrating Movements in Official Holdings of Foreign Exchange: A Rejoinder - Thorn, Richard S. (The Review of Economics and Statistics, 1965)
Richard S. Thorn, A Proposal to Remove Some Disequilibrating Movements in Official Holdings of Foreign Exchange: A Rejoinder, The Review of Economics and Statistics, Vol. 47, No. 3 (Aug., 1965), pp. 331-334